The Psychology of Workplace Deviant & Criminal Behavior - Brice, William (2015)
The 2013 book Deviant and Criminal Behavior in the Workplace addresses the psychological constructs, situations, and environments underlying active counterproductive workplace behaviors. Building on a diverse range of psychological findings, this book highlights that the field of criminology needs to expand outside of the realm of violence and instead look at how deviant workplace behaviors can tie into—and motivate—other types of crime